Novel insights into banking risk structure: Empirical evidence from nexus of financial, governance, and industrial landscape through nested tested modeling - Sabtain Fida; Muhammad Naveed (Cogent Business & Management, 2021)
The present study brings new insights to investigate the empirical estimation of banking risk behavior through advanced mechanisms. Consistent with the need to comply with the new age of finance, this study uniquely banks its case by employing nested tested modeling through a nexus of bank-specific parameters, governance mechanism, and industry dynamics. The panel estimation based on the data set of all listed Pakistani banks from 2004 to 2018 substantiates the relative significance of customized advanced econometric models to understand the banking risk structure in an integrative methodical manner. The findings manifest exacerbation of banking risk from bank-level parameters of equity investments and advances' maturity, whereas investments driving sovereign support abbreviate bank risk parametrically. The governance mechanism mainly stipulates the efficacious role of governance structures to abbreviate banking risk. Moreover, the multifarious influence of industry dynamics of concentration and munificence abridges standalone and asset return risk, whereas accelerating total risk. Industrial dynamism also adversely affects total bank risk. The applied perspective of study offers advanced working knowledge to risk managers, policymakers, and financial institutions to comprehend the risk management framework.
Keywords: 650; standalone risk; nested tested modeling; governance mechanism; industry dynamics